2001
DOI: 10.1897/1551-5028(2001)020<0502:tfpiwe>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Fungicide Propiconazole Interferes With Embryonic Development of the Crustacean Daphnia Magna

Abstract: Propiconazole is a fungicide used in a variety of agricultural applications. Preliminary studies had suggested that embryos of the crustacean Daphnia magna are particularly susceptible to the toxicity of this chemical. The goals of the present study were to define endpoints of daphnid embryonic development that could be routinely used to assess the embryo toxicity of chemicals and to characterize definitively the embryo toxicity of propiconazole to daphnids. Daphnid embryonic development was characterized into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 16 publications
4
39
0
5
Order By: Relevance
“…Several studies have reported effects of environmental chemicals that are consistent with interference with ecdysteroid signaling, though a precise mechanism of action was not established. The chemicals 4-nonylphenol [69], propiconazole [70], and bisphenol A [71], have elicited effects in crustaceans consistent with anti-ecdysteroidal activity. The fungicides propiconazole [72] and fenarimol [73] inhibit cytochromeP450 (CYP) enzymes that are critical to ecdysteroid synthesis.…”
Section: Toxicity Of Chemicals That Mediated Endocrine Disruption On mentioning
confidence: 97%
“…Several studies have reported effects of environmental chemicals that are consistent with interference with ecdysteroid signaling, though a precise mechanism of action was not established. The chemicals 4-nonylphenol [69], propiconazole [70], and bisphenol A [71], have elicited effects in crustaceans consistent with anti-ecdysteroidal activity. The fungicides propiconazole [72] and fenarimol [73] inhibit cytochromeP450 (CYP) enzymes that are critical to ecdysteroid synthesis.…”
Section: Toxicity Of Chemicals That Mediated Endocrine Disruption On mentioning
confidence: 97%
“…Additionally, severe abnormalities including abnormally shaped otic vesicle and head length were concentration-related and observed in rat embryos exposed to 10-100 µM ketoconazole (Menegola et al, 2006;Bechter and Schmid, 1987;Kucera et al, 1993). Also, propiconazole interfered with embryonic development of the crustacean Daphnia magna (Kast-Hutcheson et al, 2001). In a study by de Jong et al (2011) comparing EST, rat WEC, and the Zebrafish Embryotoxicity Test (ZET), six related triazole compounds inhibited cardiomyocyte differentiation concentration-dependently in eSt.…”
Section: Conazolementioning
confidence: 99%
“…This large batch of working solution provided a sufficient volume for dosing each appropriate test system, plus provided two additional jars for malathion concentration analysis. Although we did not perform a control for the ethanol carrier in this experiment, other experiments have documented no adverse effects of ethanol at concentrations (0.5 ml ethanol/L water) higher than those used in our study (0.41 ml ethanol/L water) on Daphnia [33]. We used a separate container to make each working solution.…”
Section: Malathion Applicationmentioning
confidence: 99%